2021
DOI: 10.1126/sciadv.abf5326
|View full text |Cite
|
Sign up to set email alerts
|

Sea level and deep-sea temperature reconstructions suggest quasi-stable states and critical transitions over the past 40 million years

Abstract: Sea level and deep-sea temperature variations are key indicators of global climate changes. For continuous records over millions of years, deep-sea carbonate microfossil–based δ18O (δc) records are indispensable because they reflect changes in both deep-sea temperature and seawater δ18O (δw); the latter are related to ice volume and, thus, to sea level changes. Deep-sea temperature is usually resolved using elemental ratios in the same benthic microfossil shells used for δc, with linear scaling of residual δw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
162
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(179 citation statements)
references
References 98 publications
12
162
5
Order By: Relevance
“…This calls for a larger contribution of deep-sea tem-peratures to the amplitude of Miocene benthic δ 18 O fluctuations. The actual strength of the impact will, however, depend on the isotopic composition of Antarctic snow as well (Gasson et al, 2016;Rohling et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This calls for a larger contribution of deep-sea tem-peratures to the amplitude of Miocene benthic δ 18 O fluctuations. The actual strength of the impact will, however, depend on the isotopic composition of Antarctic snow as well (Gasson et al, 2016;Rohling et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that these feedbacks tend to increase hysteresis in the CO 2 -equilibrium ice volume relation, and decrease the amplitude of AIS variability under equal 40-kyr forcing CO 2 cycles by 21%. This implies that correspondingly, the contribution of AIS volume changes to benthic δ 18 O fluctuations gets smaller, although the strength of the impact will depend on the isotopic composition of Antarctic snow as well (Gasson et al, 2016;Rohling et al, 2021). Furthermore, we use recent reconstructions of Antarctic bedrock topography during the Miocene (Hochmuth et al, 2020a;Paxman et al, 2019), rather than the present day as in Stap et al (2019), as a boundary condition in our AIS simulations.…”
Section: Discussionmentioning
confidence: 99%
“…4a). The clumped-isotope paleotemperatures are also compared to a (Rohling et al, 2021) to the present-day isotopic composition of Perth Basin seawater (+0.8 ‰ Vienna Standard Mean Ocean Water (V-SMOW), dashed line in Fig. 5a).…”
Section: Clumped-isotope-based Calcification Temperature Reconstructionsmentioning
confidence: 99%
“…These two forcing factors are represented in Fig. 6c by token of the eustatic sea level reconstruction by Rohling et al (2021) and the intertropical insolation gradient on 21 June (SITIG; Bosmans et al, 2015). Eustasy plays a role because sea level lowstands weaken ITF connectivity and reduce the availability of shallow Leeuwin Current source waters.…”
Section: Isotopic Gradients Along the Leeuwin Currentmentioning
confidence: 99%